HUMAN RIGHTS VS FUNDAMENTAL RIGHTS : THEORETICAL DIALECTICS OVER THE DEBATE BETWEEN UNIVERSALIST AND PARTICULARIST VIEWS - Rachminawati (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract The term “human rights” represents a universalist notion and doctrine of rights brought by the 1948 United Nations Universal Declaration of Human Rights, thus often appears to be in friction with particularistic notions of rights. Despite the Vienna Declaration 1993 purportedly settling the debate, problems appear to persist and often only escalates day after day. Here, I comparatively examine the doctrinal foundations of the “human rights” notion and compare it with the “fundamental rights” notion in how they affect the dilemma of universality versus particularism, and their impact on the enforcement and institutionalization of rights. This paper concludes by finding that the use of the term ‘fundamental rights’ instead of ‘universal human rights’ better accommodates states’ uniqueness ultimately achieving the ideals of human rights and is more acceptable to then afford more protectionAbstrak Istilah “hak asasi manusia” mewakili gagasan universal dan doktrin hak-hak yang ada dalam Deklarasi Universal Hak Asasi Manusia Perserikatan Bangsa-Bangsa 1948, dan sering kali terlihat berseberangan dengan gagasan-gagasan hak yang bersifat partikularistik. Meskipun Deklarasi Wina 1993 seolah menyelesaikan perdebatan tersebut, ternyata hari demi hari tampak masalah-masalah itu masih ada dan sering kali semakin meruncing. Tulisan ini secara komparatif menelaah landasan doktrinal dari gagasan “hak asasi manusia” dan membandingkannya dengan gagasan “hak-hak fundamental” dalam hal bagaimana gagasan tersebut memengaruhi dilema universalitas versus partikularisme, serta dampaknya pada penegakan dan institusionalisasi hak-hak. Makalah ini menyimpulkan bahwa penggunaan istilah ‘hak-hak fundamental’ daripada ‘hak asasi manusia universal’ adalah lebih baik karena dapat menyesuaikan dengan keunikan setiap negara yang pada akhirnya mencapai cita-cita hak asasi manusia, selain lebih diterima oleh negara-negara sehingga diharapkan memberikan perlindungan yang lebih besar.